2017
DOI: 10.1590/1809-4430-eng.agric.v37n4p644-655/2017
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Emergence and Initial Growth in Soil With Water Excess

Abstract: Sunflower crops are grown in different regions worldwide. However, the stress caused by water excess in the soil impairs this crop growth and yield. The aim of the present study was to determine the response of sunflower plants to long periods of water excess during initial development stages. Water excess treatments were applied at the initial development of these plants at the sowing day, three days after sowing, at plant emergence, and at V2 and V4 stages. The treatments had different duration periods (0, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…In this study, the major reduction in seedling emergence appeared for inundations of more than 24 h duration. Similar results were reported by Loose et al [30] and Albuquerque and de Carvalho [31], who demonstrated that waterlogging for 48 h and water potential in excess of 0.0001 MPa sharply depresses sunflower emergence. However, waterlogging caused a more severe reduction in seed emergence for early sown than later sown sunflower.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the major reduction in seedling emergence appeared for inundations of more than 24 h duration. Similar results were reported by Loose et al [30] and Albuquerque and de Carvalho [31], who demonstrated that waterlogging for 48 h and water potential in excess of 0.0001 MPa sharply depresses sunflower emergence. However, waterlogging caused a more severe reduction in seed emergence for early sown than later sown sunflower.…”
Section: Discussionsupporting
confidence: 89%
“…This means that sunflower is less sensitive to water stress while it is more sensitive to excess water compared to the soybean. Excess water just after sowing or germination is stressful for sunflower: it affects the seedling emergence and the dry matter content of the roots (Loose et al, 2017). We also observed the development of secondary and adventitious roots near the soil surface at 20% moisture level, which is a reaction of sunflower to excess water (Yasumoto et al, 2011).…”
Section: Heterotrophic Growthmentioning
confidence: 56%
“…Means followed by the same letter, lowercase between bars with the same color, uppercase between bars with different colors and Greek letters between leaching and sunflower cultivation, do not differ by Tukey test at p ≤ 0.05. C -control (without treatment); G -agricultural gypsum; BM -bovine manure; RH -Rice husk; CF -coconut diber; G + BMgypsum + bovine manure; G + RH -gypsum + rice husk; G + CF -gypsum + coconut fiber obtained after leaching, may have been due to the absence of leaching because the water depths applied were calculated based on crop evapotranspiration as it does not tolerate soil with a high moisture content for a long time (Loose et al, 2017). The efficiency of gypsum and organic matter in reducing soil salinity may be more related to the reaction time than the applied mass.…”
Section: Resultsmentioning
confidence: 99%